Structural characteristics and diversity of the rhizosphere bacterial communities of wild Fritillaria przewalskii Maxim. in the northeastern Tibetan Plateau - Cui, Zhijia; Li, Ran; Li, Fan; Jin, Ling; Wu, Haixu; Cheng, Chunya; Ma, Yi; Wang, Zhenheng; Wang, Yuanyuan (Frontiers in Microbiology, 2023)
Fritillaria przewalskii Maxim. is a Chinese endemic species distributed in the northeastern part of the Tibetan Plateau. Its bulbs have medicinal value as a source of the Chinese traditional cough medicine Fritillariae Cirrhosae Bulbus. Studies on the rhizosphere microbial have shown that rhizosphere microorganisms could maintain the stability of soil structure and regulate plant growth. Investigation of the rhizosphere soil from natural populations of F. przewalskii suggests that rhizosphere microbial diversity and correlates with soil properties and plant phenotypes, which is expected to provide a theoretical basis for regulating plant growth and improving plant yield. In this study, we determined the plant phenotypic characteristics of wild F. przewalskii from 12 sites within its natural range and collected soil to analyze the structural characteristics and diversity of bacterial communities in rhizosphere and bulk soil, and measure the soil physicochemical properties. Our results demonstrated that the bacterial communities varied not only between rhizosphere and bulk soil, but also among sites. Compared to bulk soil, the structure of the rhizosphere bacterial community was more complex. The alpha diversity and beta diversity of rhizosphere bacterial communities significantly varied among some sites (p<0.05). At different taxonomic levels, the composition and functional phenotypes of rhizosphere bacterial microbiome differed across sites. Both soil physiochemical and plant phenotypic characteristics significantly correlated with the bacterial community (p<0.05). Bacterial community structure was more similar in sites with similar soil properties, indicating that soil physicochemical properties were the main reason explaining community differences, with pH as a key factor. Moreover, the differences of F. przewalskii phenotypes and soil properties among sites were in turn related to the functions of specific distributed microorganisms. Interestingly, F. przewalskii seems adapted to sub-acidic soil with low potassium content soil environment, however this needs future verification. Our findings were based on comprehensive exploration of rhizosphere bacterial community in wild F. przewalskii to provide theoretical guidance and new insights to artificial cultivation and domestication of F. przewalskii.